(untitled) (San Diego, 1999)
The book describes the different types of databases, how to use a specific database to find a sequence that you need, and how to analyze the data to compare it with your own work.
Keywords: Di truyền,Genetics,Nucleotide sequence; Xử lý dữ liệu,Data processing,Databases